An evaluation of genetic variability in seedling vigour in wheat (Triticum aestivum L.) - Sarojini, Mahatma; Narayan , Ratan; Naidu, Viswanathan (Global Journal of Food and Agribusiness Management, 2017)
This experiment was aimed to study whether genetic variability exists in the seedling vigour of 50 elite spring wheat lines and also to study its correlation with yield and yield components. Analysis of variance reveals significant difference for seedling vigour index as well as other yield and yield components. The phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) was observed highest in seed yield plot-1 , vigour index, 1000-seed weight and tillers m-2 . The highest heritability accompanied with genetic advance was observed in seed yield plot-1 , seed vigour index, 1000-seed weight and spike length which is due to additive gene action and direct selection for these traits would be rewarding. Seed vigour index had significant and positive correlation with seed yield and other yield components except for spike length at both phenotypic and genotypic level. This study revealed that seed vigour index is strongly under genetic control and has great scope to be included in wheat breeding program as a selection parameter to assess stress tolerant as well as vigorous genotypes.